Need humanities be so useless? Justifying the place and role of humanities as a critical resource for performance and practice. Issue 2 (4th December 2006) - Edgar, A; Pattison, S
Abstract : Justifying the existence, position, and relevance of academic humanities scholarship may be difficult in the face of chronic practical needs in health care. Such scholarship may seem parasitic on human activity and performance that directly contributes to human wellbeing and health care. Here, a possible and partial justification for the importance of scholarship in the humanities as a critical resource for practice and performance is undertaken by two humanities scholars. Human identity and emotion are reflected and defined by performances, both in the traditional disciplines of the humanities, such as art and literature, and in the sciences and medicine. The critical attitude that such performances might inadvertently undermine is sustained by the humanities. The humanities disciplines ask the question: "What is it to be human?" Uncritical emotion and expression, arising, for example, from understanding developments in medicine and science, which might exclude or corrupt much that is of value in the healthcare sector and other areas of practical performance, can be constrained by this.